Control Electromagnetic Waves Based on Multi-Layered Transparent Metasurface - Sun, Zhichao; Yan, Mengyao; Eric Mupona, Tungamirai; Xu, Bijun (Frontiers in Physics, 2019)
Metasurface was presented to be the two-dimensional analogs of metamaterials that regulate the beam by adjusting the phase and amplitude of the wavefront. By properly designing and arranging the metasurface elements to form an array, the singularity of the metasurface to the propagation direction of the electromagnetic wave beam can be controlled; such unique electromagnetic properties offer additional opportunities to innovate new antennas. In this paper, we present the design and numerical simulation of the multi-layered microwave metasurface. The structure is designed to control the phase change of the transmission wave by changing the size of the multi-layered transparent microwave metasurface unit. Numerical simulation results show that the specific degree deflection of the electromagnetic wave is achieved in the microwave band. The design expands the application of phase gradient metasurface in the microwave field and provides a new method for metasurface electromagnetic beam steering.